Complete Genome Sequence of a Human Coxsackievirus B3 from a Child with Myocarditis in Beijing, China - Du, Jiang (American Society for Microbiology, 2013)
A human coxsackievirus B3 (CVB3), designated strain Beijing0811, was isolated from a child diagnosed with hospital-acquired infectious acute myocarditis in Beijing, China, and propagated in human rhabdomyosarcoma cells. The complete genome sequence of this virus was 7,402 nucleotides, excluding the 3′ poly(A) tail, which encoded a large polyprotein with 2,185 amino acids. This report will help us to analyze the evolutionary and epidemic characteristics of CVB3.